ANALISIS KINERJA PERUMDA AIR MINUM TIRTA RANGGA DALAM PELAYANAN AIR BERSIH KABUPATEN SUBANG - Nur Shabrina, Nabilla; Marom, Aufarul; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2024)
Perumda Air Minum Tirta Rangga Subang Regency is a Regional-Owned Enterprise that is responsible for organizing regional government affairs and is obliged to provide clean water supply services to the community. This research aims to analyze organizational performance as well as the driving and inhibiting factors of organizational performance of Perumda Air Minum Tirta Rangga Subang Regency. This research method is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis techniques carried out by data reduction, data presentation, and conclusion drawing. Sampling techniques with purposive sampling and data validity through source triangulation. The results showed that the performance of Perumda Air Minum Tirta Rangga Subang Regency was not optimal, especially in the phenomenon of productivity in providing clean water services to the community was not successful because the effectiveness did not reach the target. Aspects of service quality in the form of timeliness in handling complaints and community complaints also cannot be carried out optimally. Factors that hinder the performance of Perumda Air Minum Tirta Rangga Subang Regency are personal factors and system factors. Suggestions that researchers can convey are Perumda Air Minum Tirta Rangga Subang Regency can increase productivity by evaluating the effectiveness of services in achieving customer targets, standardizing employee recruitment, and increasing timeliness in handling complaints and community complaints.